Effects of melatonin on ginseng leaf phenotypic and photosynthetic properties following chilling and freezing stress - Deyue Su; Licai Du; Jianfeng Wang; Gang Li; Fan-li Kong (Plant Stress)
Spring frost damage is a significant natural disaster, which can lead to large-scale ginseng (Panax ginseng C. A. Mey) yield reduction. To determine chilling and freezing stress damage to ginseng, we designed an experiment using three-year-old potted ginseng plants. We simulated chilling (0 ± 0.3 ℃) and freezing (-2.5 ± 0.3 ℃, -5 ± 0.3 ℃) in an artificial room, with 16±2 ℃ of the room temperature at night as the control, to evaluate their physiological effects on ginseng leaf spectral reflectance, photosynthetic characteristics, and chlorophyll fluorescence parameters. We also investigated the mitigating effects of exogenous melatonin on ginseng leaves exposed to chilling and freezing stress. All ginseng leaves died under -5 ℃ freezing stress and the mortality rate reached 25∼57 % under -2.5 ℃ freezing stress, while no plants died under 0 ℃ chilling stress. After -2.5 ℃ and 0 ℃ stress, leaf spectral reflectance in the 750∼1000 nm band was significantly lower than the control; transpiration rate, net photosynthetic rate, intercellular CO2 concentration, and stomatal conductance decreased significantly compared with the control, and there was no significant change in recovery time. The Fv/Fm ratio and qp decreased after low-temperature stress, while NPQ increased. After one week of melatonin application, leaf spectral reflectance in the 600∼650 and 750∼1000 nm bands reflected significant differences between the effects of melatonin application and no application on ginseng leaf chlorophyll content and structure under freezing stress. Ginseng leaf net photosynthetic rate increased by 23.79 % and 4.48 %, while intercellular CO2 concentration increased by 33.49 and 11.83 % under stress at -2.5 °C and 0 °C. The ginseng leaf chlorophyll fluorescence parameter (Fv/Fm) recovered to 0.8 and above in one week after melatonin application, and qp decreased under -2.5 °C and 0 °C stress after melatonin application. Additionally, the NPQ values were 11.44 % and 4.6 % lower in -2.5+MT and 0+MT, respectively, compared to the treatment without MT applied. A sudden drop in temperature to 0 ℃ or even below caused ginseng plant growth inhibition, but melatonin application at a concentration of 100 nmol L−1 had certain mitigating effects on ginseng growth, which provides a theoretical basis and technical support for ginseng production.